Comparative characterization of key odorants and aroma profiles of fragrant rapeseed oil under different roasting conditions. (January 2023) - Zhang, Youfeng; Zhen, Cheng; Zhao, Bixi; Zhou, Shengmin; Jiang, Yuanrong; Wang, Xingguo; Jin, Qingzhe; Zhang, Yanyan
Graphical abstract: Highlights: Key odorants of fragrant rapeseed oil (FRO) were characterized by Sensomics. Dimethyl trisulfide and 4-isothiocyanato-1-butene were the most important odorants. Most odorants show a tendency to rise and then fall with intensifying roasting. Changes of the key odorants in roasting and sensorial experience were highlighted. The outcome provided a reference for sustainable FRO production with targeted aroma. Abstract: Fragrant rapeseed oil (FRO) produced by typical roasting process is popular for its characteristic aroma. Accordingly, key aroma-active compounds were characterized in FRO by the Sensomics approach and then correlated to the crucial roasting parameters revealed by aroma profile analysis and hierarchical cluster analysis. Nineteen key odorants in FRO were identified and quantified, among which dimethyl trisulfide (OAV, odor active value, 323, cabbage-like, sulfury) and 4-isothiocyanato-1-butene (OAV, 88, pungent) were the most important aroma-active compounds in FRO and showed first rising and then decline trends as the increased roasting temperature and time. The oil under high-temperature-short time and low-temperature-long time conditions imparted similar aroma profiles. On the basis of sensory evaluation, roasting at 160, 170, 180, 190, and 200 °C should not exceed 50, 40, 30, 30, and 30 min, respectively to satisfy consumer preference. All findings provide a reference on industrial FRO production in terms of not only aroma but also sustainability.